Healthcare Professional’s Knowledge about Cost Related Medication Information in Saudi Arabia - Alomi, Yousef Ahmed; Alaskari, Dima Ahmad; Almelf, Malak Mohammad; Badawi, Dima Ali; Alshihri, Abdullah Mohammad (Journal of Pharmacy Practice and Community Medicine)
Purpose: To explore the Healthcare Professionals and Knowledge of Medications cost in Saudi Arabia. Methods: It is a 4-months cross-sectional survey of healthcare professionals and knowledge of medicines. The survey consisted of two-part, demographic information and second part forty-nine questions divided into four domains. It included domain one: Primary or essential information about healthcare providers medication, domain two: healthcare professionals information about the drug-related problem, domain three: healthcare professionals information about drug-related cost and domain four: Healthcare providers perception of medications. All type of healthcare professionals included in the study. Medline Plus health information and DailyMed-INH elements information from National Institute of Health United State of America were used. The 5-point Likert response scale system was used. The questions were open and closed-ended. The survey was distributed through social media by using what’s App to more than one thousand healthcare professionals overall Kingdom of Saudi Arabia. The survey was made in an electronic format and it analyzed domain three: healthcare professional’s information about drug-related cost through survey monkey system. Results: The total responders were (188) Healthcare professionals. Of those 177 (95.16%) were Saudi and 9 (4.84%) were non-Saudi. The gender distribution 120 (63.83%) were females and 68 (36.17%) were males. The most of Healthcare professionals were pharmacist 93 (71.54%), followed by nurses 18 (13.85%) and physicians 15 (11.54%). The most type of medications used was anti-hypertension medicines, anti-diabetic medicines, Skin medications and drugs for Respiratory Diseases. Also, the most number of medications taken either one 29 (15.85%) or two 17 (9.29%). The healthcare professionals showed good knowledge with both complete and incomplete information about drug storage at room temperature 148 (81.3%) or refrigerator 143 (77.7%), protect medication from light exposures 133 (72.3%) and how to behave with an expired medication 127 (70.5%). The healthcare professionals had not adequate information with both complete and incomplete information about prescription prices 110 (59.78%) and imperfect knowledge about Health insurance coverage of medications 69 (37.9%). The healthcare professional’s knowledge about missing of medications, led patient visit doctor clinic 35 (18.72%), visit the pharmacy 50 (27.47%), visit hospital emergency 17 (9.24%) hospital admission 20 (10.87%) or intensive care admission 8 (4.79%). Conclusion: Healthcare professional missed medication-related cost knowledge. Healthcare professionals may implicate in drug-related problems with burden cost. Healthcare providers demanded of Drug-related prices and drug cost awareness program in Saudi Arabia.
Keywords: Healthcare professional; Knowledge; Ministry of Health; Saudi Arabia; Cost